Community Synergy for Clean Rivers: A Case Study on Household Waste Management in Rural Areas - Riyanti, Ika; Masruri, Masruri; Wike, Wike (Universitas Panji Sakti, 2024)
Effective waste management is a crucial responsibility of the government to protect the environment and public health. Failure in waste management, particularly in densely populated and flood-prone areas, can lead to environmental disasters such as river sedimentation and major flooding. This study aims to analyze the perceptions of the Pungpungan Village community regarding household waste management along the riverbanks and to formulate an ideal and sustainable management strategy. The research method used was descriptive qualitative. The total sample for this study comprised 40 households, which were selected through simple random sampling. In addition, purposive sampling was applied based on specific criteria to select samples according to the community's background and role. The primary data collection techniques in this study included interviews and observations. For secondary data, the research relied on literature reviews and documents, including those from the Pungpungan Village Government Office and library studies. The data analysis in this study employed SWOT analysis. The results indicate that although the community has good knowledge of the 3R concept (reduce, reuse, recycle) and the negative impacts of improper waste disposal, the practice of transforming waste into economically valuable products remains limited. The ideal strategy involves increasing education, providing infrastructure, and enforcing sanitation regulations to achieve sustainable waste management. The implications of this study suggest that a participatory approach, coupled with adequate infrastructure support facilitated by the village government, can significantly enhance the effectiveness of household waste management and encourage more sustainable behavioral changes in rural communities.